Faktor-Faktor yang Menentukan Preferensi Mahasiswa untuk Berwirausaha - sahwa setia sanggita; Dewi Rahmi (Bandung Conference Series: Economics Studies, 2024)
Abstract. Students in Indonesia have a lot of potential that can be processed and developed both from a creative perspective, however, with limited job opportunities and the difficulty of breaking through to standardization, companies in Indonesia have not been able to eradicate Indonesia from the problems of poverty and unemployment. Indonesia really needs entrepreneurs on a large scale. This research was conducted to determine the preferences of students at Bandung Islamic University in entrepreneurship, what factors determine student preferences for entrepreneurship and the dominant factors that determine student preferences for entrepreneurship. The research method in this research uses quantitative descriptive research on a Likert scale. Data collection techniques were carried out by conducting interviews with managers in the entrepreneurship sector and distributing questionnaires via Google Form to students at Bandung Islamic University. The results of this research found that the majority of students' preference was for entrepreneurship, of which 82 respondents tended to choose entrepreneurship or had a preference for entrepreneurship over becoming employees. The factors that determine student preferences are motivation, interest and environment. Where the most dominant factor determining preference is motivation which is shown by the highest total score of 334. Abstrak. Mahasiswa di Indonesia memiliki banyak potensi yang dapat diolah dan dikembangkan baik dari segi kreatif, akan tetapi dengan keterbatasan lapangan pekerjaan serta sulitnya menembus standarisasi suatu perusahaan yang ada di Indonesia belum mampu mengentaskan Indonesia dari permasalahan kemiskinan dan pengangguran. Indonesia sangat membutuhkan keberadaan para wirausaha dalam skala besar. Penelitian ini dilakukan untuk mengetahui preferensi mahasiswa di universitas islam bandung dalam berwirausaha, faktor apa saja yang menentukan preferensi mahasiswa berwirausaha dan faktor dominan yang menentukan preferensi mahasiswa berwirausaha. Metode penelitian dalam penelitian ini menggunakan penelitian deskriptif kuantitatif berskala likert. Teknik pengumpulan data dilakukan dengan melakukan wawancara kepada pengelola bidang kewirausahaan dan penyebaran kuisioner melalui google form kepada mahasiswa di Universitas Islam Bandung. Hasil penelitian ini ditemukan bahwa sebagian besar preferensi mahasiswa untuk berwirausaha, yang dimana 82 responden cenderung memilih berwirausaha atau memiliki preferensi berwirausaha dibandingkan menjadi pegawai. Faktor yang menentukan preferensi mahasiswa tersebut yaitu motivasi, minat dan lingkungan. Dimana faktor yang paling dominan menentukan preferensi adalah motivasi yang ditunjukkan nilai total skor tertinggi yaitu sebesar 334.